Possible Targets to Reduce Fatigue in Chronic Immune Thrombocytopenia Patients – An Explorative Study - van Dijk, Wobke E.M.; Nap-van der Vlist, Merel M.; Knoop, Hans; Schutgens, Roger E.G. (TH Open, 2022)
Background Fatigue in immune thrombocytopenia (ITP) is frequent and burdensome, but we lack the knowledge to help these patients.Aim The aim of the study is to explore the role of disease activity and other potentially modifiable factors in fatigue.Method This cross-sectional study included adult chronic ITP patients (n = 59). Univariable linear regression (corrected for confounders) was used to determine the relationship between disease activity (platelet count <30 × 109/L or treatment), disease-specific factors (bleeding symptoms, ferritin), and transdiagnostic factors (FACT-G physical/functional/emotional/social well-being subscales, physical activity level, and vitamin D) and fatigue (Checklist Individual Strength fatigue subscale). Several multivariable models with clustered sets of variables were used to compare the proportion of explained variance of fatigue (adjusted R2).Results Significant relations with moderate effect sizes (>0.50) were found for physical and functional well-being and fatigue, and physical activity and fatigue. Other significant relations with fatigue (effect size 0.30–0.47) included skin and organ bleeding, emotional and social well-being, vitamin D, and disease activity. Notably, the models with disease activity and disease-specific factors explained <20% of the variance in fatigue, while the models with transdiagnostic factors (functioning and physical activity) explained >50%. Vitamin D alone explained 12% of the variance in fatigue.Conclusion Transdiagnostic (non-disease-specific) rather than disease-specific factors explained a large part of the variance in ITP-related fatigue. Many factors related to fatigue are potentially modifiable and should be investigated as targets for interventions.
Keywords: fatigue; immune thrombocytopenia; modifiable factors; disease activity; transdiagnostic